How does perceived autonomy-supportive and controlling behaviour in physical education relate to adolescents' leisure-time physical activity participation? - Tilga, Henri (Array, 2020)
In line with the tenets of self-determination theory, the current study tested associations of perceived autonomy-supportive and controlling behaviour from PE teacher with adolescents’ leisure-time physical activity (LT PA) participation, and the role of need satisfaction and need frustration, autonomous motivation and controlled motivation in PE, and perceived effort towards LT PA as mediators of these associations. Adolescents (N=381) aged between 12 and 15 years completed self-reported measures of respective constructs. Results of the structural equation modelling demonstrated that perceived autonomy-supportive behaviour from PE teachers was related to adolescents’ LT PA participation only via experiences of need satisfaction and autonomous motivation in PE, and perceived effort towards LT PA. Perceived controlling behaviour from PE teachers was found to be related to adolescents’ LT PA participation only via experiences of need frustration and controlled motivation in PE, and perceived effort towards LT PA. The current study provided evidence that perceived autonomy-supportive behaviour and perceived controlling behaviour from PE teachers contributes to adolescents’ LT PA participation through unique pathways. Findings highlight the facilitative role of autonomy-supportive behaviour from teachers in a PE context on adolescents’ LT PA participation. In addition, the beneficial role of controlled motivation in PE, although instigated by students’ perceptions of controlling behaviour from teachers and experiences of need frustration in PE, on adolescents’ LT PA participation was supported.